2020
DOI: 10.1186/s12984-020-00708-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation (tDCS) for improving aphasia after stroke: a systematic review with network meta-analysis of randomized controlled trials

Abstract: Background: Transcranial Direct Current Stimulation (tDCS) is an emerging approach for improving aphasia after stroke. However, it remains unclear what type of tDCS stimulation is most effective. Our aim was to give an overview of the evidence network regarding the efficacy and safety of tDCS and to estimate the effectiveness of the different stimulation types. Methods: This is a systematic review of randomized controlled trials with network meta-analysis (NMA). We searched the following databases until 4 Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 58 publications
0
27
0
1
Order By: Relevance
“…Por otro lado, la estimulación anódica en la tDCS sobre la corteza motora primaria izquierda también presentó óptimos resultados en la comunicación funcional. Otros enfocados a la estimulación de la corteza premotora izquierda, el área motora suplementaria izquierda, región perisilviana inferior izquierda y la circunvolución inferior izquierda (24)(25)(26). Datos sorprendentes que dificultan y apoyan la tarea de dilucidar aún más los mecanismos subyacentes en este proceso de rehabilitación.…”
Section: Resultados Y Discusiónunclassified
“…Por otro lado, la estimulación anódica en la tDCS sobre la corteza motora primaria izquierda también presentó óptimos resultados en la comunicación funcional. Otros enfocados a la estimulación de la corteza premotora izquierda, el área motora suplementaria izquierda, región perisilviana inferior izquierda y la circunvolución inferior izquierda (24)(25)(26). Datos sorprendentes que dificultan y apoyan la tarea de dilucidar aún más los mecanismos subyacentes en este proceso de rehabilitación.…”
Section: Resultados Y Discusiónunclassified
“…In accordance, clinical studies applied acupuncture in the projection of the language-related brain areas, proven to have effects in improving repetition and naming functions. Previously, meta-analysis based on clinical trials suggested that the stimulation therapy over language-related brain regions was beneficial for the naming performance [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The published meta-analyses, however, due to the low quality of scientific data, did not provide sufficient evidence of the effectiveness of tDCS (k-tDCS, a-tDCS, and dual-tDCS) in improving functional communication in PSA patients, compared to the sham exposure. Nonetheless, this therapy positively influences naming [119][120][121][122]. Left IFG, right Broca's homolog, left primary motor cortex, area of the greatest left hemisphere activation, left inferior frontal cortex, right cerebellum, bilateral stimulation of left IFG and right IFG, and the left dorsolateral prefrontal cortex are brain regions that have been administered by tDCS in clinical trials [107].…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 99%
“…There were also no adverse effects and no effect of tDCS on cognitive functioning [120]. Nevertheless, a meta-analysis by Elsner et al, which aimed to determine the efficacy and safety of different stimulation subtypes (k-tDCS, a-tDCS, and dual-tDCS), showed relative efficacy in improving naming (without affecting functional communication) as a result of tDCS, and the most effective was the anodic stimulation (0.51, 95% CI 0.11-0.90), in particular of the left inferior frontal gyrus (IFG) [119]. The positive effect of tDCS on naming (endpoint) and greater effectiveness of a-tDSC compared to k-tDCS (p = 0.004) were also noted in the meta-analysis presented by Rosso et al (0.8, 95% CI 0.27-1.33, p = 0.002).…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 99%